ANALISIS POTENSI TANAH LONGSOR DI PADANGSARI BANYUMANIK SEMARANG - Setyawan, Agus; Putra, Hisbicus Dwi Surya; Suseno, Jatmiko Endro; Yulianto, Tony (BERKALA FISIKA, 2020)
Semarang city is a city that grew out of old settlement built on alluvial sediment. The conditions cause many natural disasters such as floods and landslides. Padangsari Village, Banyumanik District located in the Southern part with hilly morphology and lithology from Mount.Ungaran. Positive  potential  is  the  existences  of  material  for  development  that  are  useful  for  the community, otherwise the negative potential there is soil vulnerability than can cause landslide. Classification of positive and negative potentials is obtained from combining several data and factor  such  as:  rainfall,  slope,  groundwater  level,  lithology,  sedimentation  and  landuse.  All data were processed with ArcGis softwere and produces a potential map for the Padangsari Village. Hopefully the map will be useful for research and society in Padangsari to produce policy when infrastructure development.Keywords:  Landuse,  landslide,  rainfall,  slope,  groundwater  level,  lithology,  sedimentation, Padangsari